2011
DOI: 10.1364/oe.19.025143
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical vector beams for rapid polarization-dependent measurements in atomic systems

Abstract: Abstract:We demonstrate the use of cylindrical vector beams -beams with spatially varying polarization -for detecting and preparing the spin of a warm rubidium vapor in a spatially dependent manner. We show that a modified probe vector beam can serve as an atomic spin analyzer for an optically pumped medium, which spatially modulates absorption of the beam. We also demonstrate space-variant atomic spin by optical pumping with the vector beams. The beams are thus beneficial for making singleshot polarization-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…At the fiber input, the waveguide is in the weakly guiding regime, described by the LP-basis, with negligible longitudinal field and near unity overlap with superposition of the free-space propagation Hermite-Gauss (HG) or Laguerre-Gauss (LG) modes. By tailoring an incident Gaussian beam with spatial light modulators Frawley et al (2012b) or appropriate phase plates and mode conversion Ravets et al (2013b);Fatemi (2011), we can efficiently and selectively excite and control specific modes (or their superpositions) in the nanofiber waist Hoffman et al (2015). Diagnostics of light propagation within the nanofiber using Rayleigh scattering Hoffman et al (2015) or near-field detection Fatemi et al (2017) have shown that mode discrimination is possible even in the subwavelength region of the waist.…”
Section: Higher-order Modesmentioning
confidence: 99%
“…At the fiber input, the waveguide is in the weakly guiding regime, described by the LP-basis, with negligible longitudinal field and near unity overlap with superposition of the free-space propagation Hermite-Gauss (HG) or Laguerre-Gauss (LG) modes. By tailoring an incident Gaussian beam with spatial light modulators Frawley et al (2012b) or appropriate phase plates and mode conversion Ravets et al (2013b);Fatemi (2011), we can efficiently and selectively excite and control specific modes (or their superpositions) in the nanofiber waist Hoffman et al (2015). Diagnostics of light propagation within the nanofiber using Rayleigh scattering Hoffman et al (2015) or near-field detection Fatemi et al (2017) have shown that mode discrimination is possible even in the subwavelength region of the waist.…”
Section: Higher-order Modesmentioning
confidence: 99%
“…8 (left))) we can see that by doubling the beam waist, and hence increasing z R by a factor 4, the rotation of the larger beam is correspondingly decreased by a factor 1/4. While many applications of cylindrical vector beams use spatially-varying linear polarization (radial or azimuthal), beams with azimuthally-varying elliptical polarization allow the space-variant spin in the beam to be transferred to the atomic medium, thus offering a unique way to manipulate atoms spatially [12]. Such elliptically polarized FSL beams can be produced by changing the relative amplitudes of the two eigenmodes of a cylindrical vector beam (i.e.…”
Section: Control Of Polarization Rotationmentioning
confidence: 99%
“…The resultant beam has non-uniform spatial intensity, phase and polarization distributions. The ability to control both the spatial intensity and the polarization distribution of the optical field is of use in material processing [4]), in STED and confocal microscopy [5][6][7][8], in optical trapping and manipulation [9,10], in atomic state preparation, manipulation, and detection [9,11,12], in optical communications [13,14] and even classical entanglement [15][16][17]. Additionally, novel focussing properties associated with particular polarization distributions can lead to tighter focussing [18] and strong axial field components that are of use in microscopy [5,6], optical trapping [9], and as a mechanism for linear accelerators [19].…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of works have been reported on the measurement of the Mueller matrix with general polarimetry configurations consisting of a polarization state generator (PSG) and a polarization state analyzer (PSA), in which straightforward relations of polarization parameters to the measurements are available. Different PSG and PSA schemes have been studied with SOP generated either in time series or in spatial series [17][18][19][20][21]. In this paper, we adopt the idea of system estimation in fiber systems to measure physical polarization parameters by solving nonlinear system estimation equations with the well-known least squares (LS) numerical method.…”
Section: Introductionmentioning
confidence: 99%